A Reasoned Analysis of the Political Situation of Pakistan in the Context of Masnavi "Pas Che Baid Kurd" (An Overview) - Hashmi, Talib Hussain; Zaidi, Syed Shiraz Ali (sourcecoder, 2024)
In the Masnavi, “Pas Cha Byad Kerd”, Iqbal has criticized the political situation of his time under the title of “Current Politics”. In it, Allama Iqbal, while addressing the nations of the East, said that in today's situation, the problems facing the Muslim Ummah can be solved. That their seriousness has increased. More than seventy six years have passed since the establishment of Pakistan. We have not been able to adopt the democratic traditions which are in accordance with Islamic teachings and Iqbal's thought. The purpose of our independence was to establish a modern Islamic state, so every nation or country that is against Islam is also against Pakistan. A series of conspiracies has been going on since then. The only solution to all these conspiracies is that we should turn to Islam again and embarrass the dream of the artist of Pakistan.